A Great Communication Organization make a Perfect Organizations: Case Study at Government Public Relations - Atlisiaji, Widya Yusti (MUHARRIK: Jurnal Dakwah dan Sosial, 2022)
The intention and purpose of this scientifict article is to collect, summarize and conclude scientific events written by previous researchers to be studied. So it can be useful for future organizational life. This research studies organizational communication and the creat of a strong, healthy and perfect organization. The author uses netnography methods by google scholar to search for data using the keywords Communication organization, Government Public Relations, organization and use ebook Miller, Katherine. 2012. Organizational Communication: Approaches and Processes. 6th Ed. Boston: Wadsworth Cengage Learning. The core topic is elements in organizational communication that can create a healthy, precise and perfect organization. In this scientifict journal the author has succeeded in finding a link between organizational communication and the creation of an organization. Better organizational communication in an organization, can create the stronger, healthier and more perfect the organization.